2007
DOI: 10.14411/eje.2007.035
|View full text |Cite
|
Sign up to set email alerts
|

The role of fungal taxa and developmental stage of mushrooms in determining the composition of the mycophagous insect community in a Japanese forest

Abstract: Abstract. We hypothesize that differences in fungal taxonomic groups may exert a direct influence on the composition of mycophagous insect communities, and that the relative importance of taxonomy compared to other fungal traits may change as the mushrooms decay. We conducted a 3-year field survey and analyzed the species composition of mycophagous insect communities using partial canonical correspondence analysis (partial CCA). We collected 2457 mushrooms belonging to 27 genera, and 4616 insects belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Thus, the use of soft or tough fungi could be related to the larval development time of each beetle species (Leschen , Yamashita & Hijii ). Because each insect species needs a certain developmental time to complete its life cycle (Martinkova & Honek ), longevity (and by extension, consistency) likely matters considerably in host choice (Yamashita & Hijii , Thorn et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of soft or tough fungi could be related to the larval development time of each beetle species (Leschen , Yamashita & Hijii ). Because each insect species needs a certain developmental time to complete its life cycle (Martinkova & Honek ), longevity (and by extension, consistency) likely matters considerably in host choice (Yamashita & Hijii , Thorn et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite similarities between insect–plant and insect–basidiome interactions and the fact that insect consumption of fungi appears to be an older feeding habit than plant consumption (Gillott ), only a few studies have investigated the factors affecting the structure of assemblages of fungivorous insects (see review by Schigel ). Furthermore, with the exception of the tropical examples mentioned earlier, most of the literature focuses on interactions in temperate and boreal regions, in the Holarctic ( e.g., Jonsell & Nordlander , , Yamashita & Hijii , , Orledge & Reynolds , Epps & Arnold , Jonsell et al . ).…”
mentioning
confidence: 99%
“…Nevertheless, the potential reward for new insights into the spatial patterns of fungal fruiting is high. Fruiting is a basic biological process of many fungi, and fruit body production is an important part of ecosystems and food webs (Maser et al , Komonen , Schigel , Komonen et al ), with groups of organisms that depend on fungal fruit bodies for food and/or habitat, such as insects, mammals, slugs and snails (Wheeler and Blackwell , Worthen , Claridge and May , Yamashita and Hijii ). Several studies have shown that the timing of fungal fruiting can be driven by climatic variability at local (Sato et al , Büntgen et al , Ágreda et al ), regional (Gange et al , Diez et al ), and national (Kauserud et al , , ) scales.…”
mentioning
confidence: 99%
“…Almost all studies on mycophagous drosophilids have been conducted in North America, Europe and Japan (COURTNEY et al, 1990;BURLA et al, 1991;TODA et al, 1999;YAMASHIDA & HIJII, 2007), and indicate that Drosophila is a genus that abounds in fungi fruiting bodies, and that it may even represent the majority of Diptera that emerge from this substrate (TODA et al, 1999). These investigations also offer evidences that most mycophagous Drosophila species known belong to the pinicola, quinaria, testacea and tripunctata species groups, all of which are included in the immigranstripunctata radiation (REMSEN & O'GRADY, 2002;MARKOW & O'GRADY, 2005).…”
mentioning
confidence: 99%